Performance of locally produced cold-formed steel sections for roof truss system - Md. Tahir, Mahmood; Thong, Chin Mun; Tan, Cher Siang (Penerbit UTM Press, 2005)
Traditionally, Timber Is Usually Used For Roof Truss As A Construction Material. However, The Use Of Timber Is No Longer Popular Recently Due To The Increase In Cost, Not Environmental friendly As More Trees Need To Be Cut, Prone To Termite Attack, And Lesser Capacity Compared With Steel. Cold-Formed Steel Section Has Been Introduced In This Paper For The Construction Of Roof Truss System As An Alternative To Timber Truss. This Paper Describes Experimental Test Results Of The Proposed Cold-Formed Produced Locally With The Code Of Practice As Prescribed By BS 5950 Part 5: 1987 For The Use In Roof Truss System. The Tests Were Also Performed To Meet The Requirements That Have Been Outlined By Public Works Department, Malaysia. The Experimental Results Showed Good Agreement With BS 5950 Part 5. From The Study It Can Be Concluded That The Proposed Locally Produced Cold-Formed Steel Sections And The Connections Are Suitable To Be Used In The Roof Truss System Provided That The Design Values Should Not Be More Than The Experimental Values.